2018
DOI: 10.1002/dmrr.2973
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of olfaction and taste function in type 2 diabetic patients with and without peripheral neuropathy

Abstract: In conclusion, this study demonstrates that T2DM is associated with olfactory and gustatory dysfunction. The fact that there was no difference between the diabetic patients with and without DPN elicits the idea of central neuropathy. This novel finding might facilitate the addition of olfactory and gustatory tests to the methodological spectrum of afferent pathway investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
(58 reference statements)
1
26
0
Order By: Relevance
“…The association between olfactory function and diabetes did not vary by diabetes subtype. Among the six articles that demonstrated a statistically significant association between diabetes and OI, three studies specifically evaluated participants with T2D, while two studies did not distinguish diabetes subtype, and a single study characterized both T1D and T2D patients. Among the five articles that did not find a statistically significant association between diabetes and olfactory function, a single study evaluated T1D and T2D, two studies did not specify subtype, one study examined T1D only, and one study examined T2D only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between olfactory function and diabetes did not vary by diabetes subtype. Among the six articles that demonstrated a statistically significant association between diabetes and OI, three studies specifically evaluated participants with T2D, while two studies did not distinguish diabetes subtype, and a single study characterized both T1D and T2D patients. Among the five articles that did not find a statistically significant association between diabetes and olfactory function, a single study evaluated T1D and T2D, two studies did not specify subtype, one study examined T1D only, and one study examined T2D only.…”
Section: Resultsmentioning
confidence: 99%
“…Sniffin' Sticks was the most common method for assessment of olfactory function (6, 55%), wherein odors are presented as felt‐tipped pens with multiple choice answer options, with extended versions providing measures for odor threshold, discrimination, and identification. Additional validated measures of olfaction included the Scandinavian Odor Identification Test, Brief Smell Identification Test, and the butanol threshold test …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cross‐sectional studies conducted in recruited diabetic patients indicated several factors as being potentially explanatory or unrelated with lowered olfactory function in diabetic people . Details are presented in Supplementary Table and it is clearly visible that results of cited studies are not consistent.…”
Section: Discussionmentioning
confidence: 93%
“…Decrease in taste occasionally influences swallowing dysfunction . Because gustatory function is impaired in various neurological disorders including Alzheimer's disease, diabetic neuropathy and amyotrophic lateral sclerosis, the sense of taste should be evaluated during rehabilitation of swallowing for persons with dysphagia.…”
Section: Introductionmentioning
confidence: 99%